TLR3, TLR4 and TLRs7–9 Induced Interferons Are Not Impaired in Airway and Blood Cells in Well Controlled Asthma - Sykes, Annemarie; Edwards, Michael R.; Macintyre, Jonathan; del Rosario, Ajerico; Gielen, Vera; Haas, Jennifer; Kon, Onn Min; McHale, Mark; Johnston, Sebastian L. (PloS one, 2013)
Defective Rhinovirus induced interferon-β and interferon-λ production has been reported in bronchial epithelial cells from asthmatics but the mechanisms of defective interferon induction in asthma are unknown. Virus infection can induce interferon through Toll like Receptors (TLR)3, TLR7 and TLR8. The role of these TLRs in interferon induction in asthma is unclear. This objective of this study was to measure the type I and III interferon response to TLR in bronchial epithelial cells and peripheral blood cells from atopic asthmatics and non-atopic non-asthmatics. Bronchial epithelial cells and peripheral blood mononuclear cells from atopic asthmatic and non-atopic non-asthmatic subjects were stimulated with agonists to TLR3, TLR4 & TLRs7-9 and type I and III interferon and pro-inflammatory cytokine, interleukin(IL)-6 and IL-8, responses assessed. mRNA expression was analysed by qPCR. Interferon proteins were analysed by ELISA. Pro-inflammatory cytokines were induced by each TLR ligand in both cell types. Ligands to TLR3 and TLR7/8, but not other TLRs, induced interferon-β and interferon-λ in bronchial epithelial cells. The ligand to TLR7/8, but not those to other TLRs, induced only type I interferons in peripheral blood mononuclear cells. No difference was observed in TLR induced interferon or pro-inflammatory cytokine production between asthmatic and non-asthmatic subjects from either cell type. TLR3 and TLR7/8,, stimulation induced interferon in bronchial epithelial cells and peripheral blood mononuclear cells. Interferon induction to TLR agonists was not observed to be different in asthmatics and non-asthmatics.